On the light deflection and perihelion precession by BBMB black holes in HPM approximation - Shchigolev, Victor Konstantinovich (International Journal of Scientific World, 2023)
In this paper, the homotopy perturbation method (HPM) is applied for calculating the weak deflection angle and the perihelion precession angle of planetary orbits in the gravitational field of Bocharova-Bronnikov-Melnikov-Bekenstein (BBMB) black hole. Follow the procedure of HPM, we obtain the approximate solutions for the null and time-like geodesics in the gravitational field of BBMB black hole. On the basis of these solutions and the general formulae for the angle of deflection and the perihelion precession angle, derived by the author earlier via HPM, the corresponding angles for the BBMB black hole are obtained and compared with the similar angles in Schwarzschild spacetime. Notably that if the deflection angle obtained in this article using the HPM confirms the results of other researchers, then the perihelion precession angle obtained here for the first time can be compared with those known for a classical non-rotating static black hole.